0033 Sleep Loss-induced Anxiety- And Depressive-like Behaviors Are Attenuated In Mice Lacking Nlrp3 Inflammasomes. (27th April 2018) - Zielinski, M R; Gerashchenko, D; Basheer, R; Strecker, R E; Niznikiewicz, M M; Johnston, A M
Abstract: Introduction: Enhanced expression of pro-inflammatory cytokines including interleukin (IL)-1beta and IL-18 are associated with increased anxiety- and depressive-like behaviors. The nucleotide-binding domain leucine rich family pyrin containing 3 (NLRP3) inflammasome is a protein complex which converts IL-1beta and IL-18 into their active somnogenic forms and is enhanced after sleep deprivation. We aimed to determine the role of NLRP3 in anxiety- and depressive-like behaviors in mice. Methods: NLRP3 knockout (KO) and wild-type (WT) mice were sleep deprived for 6 h or allowed to sleep ad libitum. Thereafter, mice were exposed to the elevated-plus maze and open-field test to test anxiety-related behaviors and the tail suspension test to determine depressive-like behavior. Additional mice were sacrificed after sleep deprivation or control treatments, perfused and their brains were collected for immunohistochemistry using antibodies for IL-1beta, IL-18, NLRP3, microglia (anti-CD11b) and neurons (anti-NeuN). Additionally, the amygdala was taken for IL-1beta, IL-18, and NLRP3 gene expression analysis. Results: Sleep deprivation reduced the time in the open arms of the elevated-plus maze (p=0.023) and the time in the inner zone of the open-field test (p=0.038) (indicators of increased anxiety-like behavior) in WT but not NLRP3 KO mice. KO mice had responses after sleep deprivation that was similar to their control responses. For example, NLRP3 KO mice also did not demonstrate the significant enhanced percentage of time spent immobilized during the tail suspension test (an indicator of increased depressive-like behavior) found in WT mice (p<0.001). In the amygdala, the expression of IL-1beta, IL-18, and NLRP3, and IL-1beta, IL-18, and NLRP3 immuno-reactive microglia and neurons were elevated ( 30% or greater) after sleep deprivation in WT but not NLRP3 KO mice. Conclusion: These data suggest that the sleep deprivation-induced NLRP3 inflammasome activation of inflammatory cytokines in the amygdala contributes to detriment in anxiety and depression occurring from sleep loss. Support (If Any): Veterans Affairs I01RX00928 (MRZ), I01BX001404 (RB), I01BX002774 (RES)